Translineação em enunciados escritos infantis - Notari, Viviane Favaro (2017)
Based on the conception of constitutively heterogeneous writing such as proposed by Corrêa (2001, 2004), on this study, we have the hypothesis that, even though the hyphenation is a typical and exclusive process from the written utterances, on hyphenations made by children, it is possible to observe the emergence of children's different social and historical experiences with the spoken and written utterances types and, in a privileged way, the social and historical experiences related to the internal organization of the phonological syllable and to the conventional functioning of the orthographic syllable. From this hypothesis, our objective was to longitudinally investigate the hyphenation (conventional or not) present in utterances produced by children in the writing acquisition process considering its occurrences throughout the (previous) four first grades of elementary school and examining tendencies and particularities involved in those emergences. In a specific way, we aimed to (a) verify if there are qualitative or quantitative changes in the way children hyphenate, considering the four first grades of elementary school; (b) investigate how the (conventional or not) hyphenation proposed the children would be related to the internal organization of the phonological syllable and the connection between such organization with the conventional functioning of the orthographic syllable; and (c) examine which other factors may be involved in the emergence of hyphenations made by the child. In order to fulfill the objective, we used as the material for analysis 3131 written utterances which compose the textual production database from the study groups (CNPq) Writing acquisition studies and Language studies. In the quantitative investigation of this material, we observed that 776 utterances presented division of word in the end of the line; on these, we found 1356 occurrences of hyphenation, being 941 (69,4%) conventional ones and 415 (30,6%) not conventional ones. By considering these numbers according to the school grading, we obtained the following results: 145 (75,12%) not conventional and 48 (24,88%) conventional occurrences on the first grade; 113 (33,83%) not conventional and 221 (66,17%) conventional occurrences on the second grade; 75 (22,80%) not conventional and 254 (77,20%) conventional occurrences on the third grade; 82 (16,40%) not conventional and 418 (83,60%) conventional occurrences on the fourth grade. With these results, it was possible to verify a progressive process on the conventional registrations and a regressive process on the not conventional registrations of hyphenation. Qualitatively, we were able to observe that the hyphenations: (1) are, indeed, directly connected to the internal organization of the phonological syllable and to the relation of this organization with the conventional functioning of the orthographic syllable (presenting separations in contexts of correspondence and of not correspondence between orthographic and phonologic syllable, as well as in the split in the organization of these syllables); (2) involve factors of different natures in their emergence (related, mainly, to the grapheme/phoneme relation, to the segmentation and to semantic criteria); lastly (3) allow an observation of the construction of an imagery about writing.